2016
DOI: 10.1038/nclimate2862
|View full text |Cite
|
Sign up to set email alerts
|

Climate change stories and the Anthroposcenic

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In the Fall of 2013, Ellie Irons taught a course in art practice on the ‘Artist in the Anthropocene’ at the City University of New York. In 2014, at the Taipei Biennial, curator Nicolas Bourriaud subtitled the entire exhibition ‘Art in the Age of the Anthropocene’ and noted, in an interview, that ‘the sphere of interhuman relations cannot be conceived any more without its environmental and technological sides.’ In March 2015, a panel discussion and exhibition were organized at the University of Miami entitled ‘AnthropoScene: Art and Nature in a Manufactured Era,’ and in 2016, David Matless recommended the use of the term ‘anthroposcenic’ as a semantic term for telling stories about changing landscapes. In Berlin, the Haus der Kulturen der Welt carried out a 2‐year long project involving music, the arts, intellectual debates, and workshops around the Anthropocene theme…”
Section: What Then Is the Art Of The Anthropocene?mentioning
confidence: 99%
“…In the Fall of 2013, Ellie Irons taught a course in art practice on the ‘Artist in the Anthropocene’ at the City University of New York. In 2014, at the Taipei Biennial, curator Nicolas Bourriaud subtitled the entire exhibition ‘Art in the Age of the Anthropocene’ and noted, in an interview, that ‘the sphere of interhuman relations cannot be conceived any more without its environmental and technological sides.’ In March 2015, a panel discussion and exhibition were organized at the University of Miami entitled ‘AnthropoScene: Art and Nature in a Manufactured Era,’ and in 2016, David Matless recommended the use of the term ‘anthroposcenic’ as a semantic term for telling stories about changing landscapes. In Berlin, the Haus der Kulturen der Welt carried out a 2‐year long project involving music, the arts, intellectual debates, and workshops around the Anthropocene theme…”
Section: What Then Is the Art Of The Anthropocene?mentioning
confidence: 99%
“…Interest in unfolding the origin and nature of the Anthropocene has trespassed geohistorical sciences, and has also been approached by anthropologists, politicians, artists, philosophers and educators who embrace manifold connotations about the interaction between environment, society and culture (see Autin, 2016;Descola, 2013;Lewis and Maslin, 2015;Matless, 2016;Toivanen et al, 2017). As a consequence, there is a pressing need to prioritize a cross-disciplinary agenda for answering contingent questions such as: how did we get here?, are there regional expressions of the Anthropocene?, how do these regional manifestations add up to a global phenomenon?, how have idiosyncratic behaviors contributed?…”
mentioning
confidence: 99%
“…Many studies have similarly cautioned against uncritical acceptance of the utility of traditional knowledge in the face of the "nonlinear and stepped changes" associated with climate change (Adger et al, 2011, p. 764;Wittrock et al, 2010). A mounting body of research within this field has nonetheless suggested that the integration and co-production of traditional and scientific knowledge can be a valuable mechanism in raising awareness of, and dealing with, climaterelated uncertainty, and for reconciling the global scale of climate change with local-scale entanglements of weather and place (Brace and Geoghegan, 2011;Flint et al, 2011;Matless, 2016;Nakashima et al, 2012).…”
Section: Pathways Of Change and Responsementioning
confidence: 99%